Hydrogen sensing performance investigations with optical heating and sensing element surface modification. (1st January 2021) - Ye, Zhuang; Li, Zhi; Dai, Jixiang; Qin, Yuhuan; Wang, Gaopeng; Yuan, Zihui; Yang, Minghong
Abstract: Fiber optic hydrogen gas sensors with low detection limit and high precision are highly demanding nowadays. Self-referenced fiber Bragg grating (FBG) hydrogen gas sensor offers promising advantages due to its improved systemic stability and compactness. Nevertheless, the low sensitivity and the low stability of hydrogen sensitive materials still greatly limit its detection capability in extremely low concentration range. Here we demonstrate that an improved self-referenced FBG hydrogen gas sensor design can overcome this limitation. It is based on an integrated architecture which combines a FBG structure coated with polyaniline modified WO3 –PdPt composite film and an optical heating device using a high-power laser source. Due to the higher working temperature and the protective coating structure of the PdPt catalytic layer, the sensor shows faster response and higher measurement stability, which together results in a significantly low detection limit down to 4.5 ppm in air. These greatly improved sensing hydrogen gas performances highlights its promising applications in future. Highlights: A FBG sensor that combines system and material optimization was firstly proposed. Optical-heating is designed to impair signal fluctuation and ensure stability. Polyaniline is adopted to protect the catalytic layer and enhance sensitivity. The novel sensor shows an extraordinary hydrogen detection limit as low as 4.5 ppm.